Maturational effect on physical capacities and anabolic hormones in under-16 elite footballers: a cross-sectional study - Eskandarifard, E.; Silva, R.; Nobari, H.; Clemente, F. M.; Perez-Gomez, J.; Figueiredo, A. J. (Sport Sciences for Health, 2022)
Purpose The purposes of this study were to describe the fitness and hormonal levels according to playing time (PT) (i.e., PT during season less (PT1) or more (PT2) than 50% of the total time) and maturation level (ML) (i.e., normal (ML1) and early maturity levels (ML2)), and to analyze the differences between groups for the measures of aerobic capacity, anaerobic power, power performance, and hormonal concentrations.